Saúde nas fronteiras: acesso e demandas de estrangeiros e brasileiros não residentes ao SUS nas cidades de fronteira com países do MERCOSUL na perspectiva dos secretários municipais de saúde Health on the borders: access to and demands on the Brazilian National Health System by foreigners and non-resident Brazilians in cities along the border with MERCOSUR countries from the perspective of municipal health secretaries - Ligia Giovanella; Luisa Guimarães; Vera Maria Ribeiro Nogueira; Lenaura de Vasconcelos Costa Lobato; Giseli Nogueira Damacena (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2007)
No contexto de formação de mercados comuns, as regiões de fronteira adquirem especial atenção, pois antecipam efeitos dos processos de integração. Nas fronteiras convivem diferentes sistemas políticos, monetários, de segurança e proteção social, e a intensificação de fluxos decorrentes da integração gera novos desafios para os sistemas de saúde, exigindo políticas específicas direcionadas à garantia do direito à saúde nas regiões fronteiriças. Este trabalho apresenta resultados de pesquisa com o objetivo de analisar condições de acesso e demandas por serviços de saúde em cidades fronteiriças do MERCOSUL. Foi realizado inquérito com secretários municipais de saúde das 69 localidades brasileiras da linha de fronteira com países do MERCOSUL referentes aos Estados do Rio Grande do Sul, Santa Catarina, Paraná e Mato Grosso do Sul. Buscou-se identificar ações demandadas pela população fronteiriça, mecanismos utilizados para acesso, fluxos entre serviços e sistemas, estratégias de resposta e acordos locais. Iniciativas de cooperação entre gestores locais brasileiros e estrangeiros, identificadas em quase metade dos municípios, podem orientar a formulação de diretrizes para situações de fronteira que possibilitem a melhoria do acesso integral à atenção à saúde. In the context of forming common markets, border areas require special attention, since they anticipate the effects of integration processes. Along borders, different political, monetary, security, and social systems coexist; the intensification of flows resulting from integration raises challenges for the health systems, requiring specific policies focused on guaranteeing the right to health. This article presents the results of a study on the conditions for access to (and demands for) health services in the MERCOSUR border cities. A survey was performed with municipal health secretaries in the 69 Brazilian cities in the States of Rio Grande do Sul, Santa Catarina, Paraná, and Mato Grosso do Sul that border on the other MERCOSUR countries. The study attempted to identify the services demanded by the border population, mechanisms used for access, flows between services and systems, response strategies, and local agreements. Initiatives for cooperation between Brazilian and foreign local administrators were identified in nearly half of the municipalities and can orient the formulation of guidelines for border situations, allowing improvement in comprehensive access to health care.